2017
DOI: 10.5395/rde.2017.42.4.301
|View full text |Cite
|
Sign up to set email alerts
|

The effects of autoclave sterilization on the cyclic fatigue resistance of ProTaper Universal, ProTaper Next, and ProTaper Gold nickel-titanium instruments

Abstract: ObjectivesIt was aimed to compare the cyclic fatigue resistances of ProTaper Universal (PTU), ProTaper Next (PTN), and ProTaper Gold (PTG) and the effects of sterilization by autoclave on the cyclic fatigue life of nickel-titanium (NiTi) instruments.Materials and MethodsEighty PTU, 80 PTN, and 80 PTG were included to the present study. Files were tested in a simulated canal. Each brand of the NiTi files were divided into 4 subgroups: group 1, as received condition; group 2, pre-sterilized instruments exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Since NiTi properties are highly influenced by thermomechanical processing, the effects of additional heat retreatment promoted during autoclaving procedures can affect the mechanical properties of these instruments. This issue has been demonstrated in previously published studies that showed the influence of autoclave sterilization on the cyclic fatigue strength of NiTi instruments [7,9,11,12]. However, these findings remained controversial.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Since NiTi properties are highly influenced by thermomechanical processing, the effects of additional heat retreatment promoted during autoclaving procedures can affect the mechanical properties of these instruments. This issue has been demonstrated in previously published studies that showed the influence of autoclave sterilization on the cyclic fatigue strength of NiTi instruments [7,9,11,12]. However, these findings remained controversial.…”
Section: Introductionmentioning
confidence: 89%
“…An overall of 203 studies was retrieved. The title and abstract reading resulted in 10 studies [4,7,[9][10][11][12][15][16][17][18] that matched the eligibility criteria. No additional study was included after the manual search of the references of these 10 studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations